Exploring the real cause of hemoptysis: A case of pulmonary tumor embolism in a young woman with accompanying pulmonary metastasis of gestational trophoblastic neoplasia - Qun Hu; Meiqian Li; Yu Liu; Min Xie; Lan Wang (Pulmonary Circulation, 2023)
Abstract We report a case of pulmonary embolism caused by gestational trophoblastic neoplasia (GTN) accompanied by pulmonary metastasis to improve the recognition ability of the disease in young female patients with pulmonary embolism and hemoptysis.